Gender related factors affecting implementation fidelity of Mass Drug Administration of Lymphatic Filariasis Programme in Jhapa district of Nepal: An Implementation Research - Khanal, Shreya; Murhandarwati, Elsa Herdiana; Padmawati, Retna Siwi (BKM Public Health and Community Medicine, 2024)
Purpose: This study explores gender related factors affecting implementation fidelity of Mass Drug Administration (MDA) of lymphatic filariasis programme in Jhapa, Nepal. Method: Implementation research was conducted using an explanatory sequential design. For quantitative study, valid secondary data was used. For qualitative study, primary data will be collected from 46 respondents including community members and healthcare providers. Result: Only 77.66% epidemiological coverage was reached during MDA conducted in 2023. Both males and females over the age of two were included in the coverage, with females making up 51.01%. The lowest coverage of 46.24% and 79.81% was found among each urban and rural municipalities, respectively. Further, the qualitative data expects to identify underlying gender-related factors justifying the inequitable coverage among municiplaities, between gender and age groups that influences potential moderators in accessing resources, program adherence influenced by gender roles, social norms and values, and decision-making power in healthcare among men and women in urban and rural areas. Thus, the study results expects to provide crucial insights into how gender interacts with potential moderators of implementation fidelity in programme adherence. A study in Nepal's western terai region found that educated individuals, men working away from home as the household breadwinner, elderly individuals, urban communities, and those with chronic illnesses are more likely to miss or refuse mass drug administration (MDA) due to concerns about drug safety and lack of knowledge. Some community members also lack trust in female community health volunteers due to their lower levels of education and training, leading to lower program adherence rates due to persistent gender barriers. Conclusion: The findings obtained from this study will assist in making evidence-based decisions to address gender disparities and inequitability in accessing and utilizing interventions implemented by national neglected tropical disease programs.